Changes in biomarker abundances and sulfur isotopes of pyrite across the Permian-Triassic (P/Tr) Schuchert Dal section (East Greenland) - Fenton, Stephen; Grice, Kliti; Twitchett, R.; Bottcher, M.; Looy, C.; Nabbefeld, Birgit (Elsevier Science BV, 2007)
In this study, we report on biomarker abundances through parts of the Permian/Triassic boundary (PTB) of Schuchert Dal (East Greenland) that contains rich marine faunal records and excellent terrestrial palynological records. Biomarker abundances and sulfur isotopes are used to correlate the series of events (including changes in element cycling and associated redox conditions of the ocean) surrounding the collapse of the marine and terrestrial ecosystems through this record of a major crisis of life on Earth during a mass extinction episode. The Upper Schuchert Dal Formation contains a low diversity palynological assemblage, ascribed to arborescent cordiaite–conifer–pteridosperm vegetation. Samples from this pre-collapse interval are characterised by high abundances of dibenzofuran (DBF), dibenzothiophene (DBT) and biphenyl. Since these compounds have similar base structures, and show comparable abundance curves, it is plausible that they probably derive from a common source. We propose that phenolic compounds of lignin of the woody plants present during this period could be the source for DBF, DBT and biphenyl. The redox conditions during this period of time also support the formation of DBF and DBT. Just above the extinction interval, there is a dramatic decrease in the abundances of DBF and DBT which occurs at the same time as a sudden change in the stable sulfur isotopic composition (δ34S) of pyrite, indicating a change in redox conditions from oxic to anoxic/euxinic conditions. δ34S values leading up to the extinction are highly depleted in the heavy sulfur isotope (about − 40‰ vs. VCDT), whilst shortly after the extinction interval much more positive isotope values are observed (about − 25%). An inferred change in the biogeochemical sulfur cycle is supported by facies evidence from similar neighbouring sections. It is suggested that two processes are operating closely here; 1) Changes in redox conditions and 2) extinction and/or transgression accounting for the absence of woody material.